Dear peace - Lapira, Kris Brown Norman; Datumanong, Diagandhi; Communication Foundation for Asia.; Evangelischer Entwicklungsdienst E.V. (Manila Communication Foundation for Asia, 2007)
A half-hour documentary on the unique peace communication process involving Christian and Muslim high school students who forged friendships and reconciliation after participating in a Peace Camp and workshops organized by CFA.
Summary from www.cfa.org.
"Bonus feature: Postcript: 2.5 years later (a special report), 11 min., [Dec. 22, 2008]"--Container.
Kris Brown Norman Lapira, Diagandhi Datumanong
DVD.
In Filipino with English subtitles.
Keywords: Catholic Church -- Philippines; Religion -- Criticism, interpretation, etc; Peace -- Religious aspects -- Islam; Peace -- Religious aspects; Peace movements; Peace movements -- Religious aspects